CuInGaSe2 nanoparticles by pulsed laser ablation in liquid medium. (December 2015) - Mendivil, M.I.; García, L.V.; Krishnan, B.; Avellaneda, D.; Martinez, J.A.; Shaji, S.
Graphical abstract: Highlights: CIGS nanocolloids were synthesized using PLAL technique. Characterized their morphology, structure, composition and optical properties. Morphologies were dependent on ablation wavelength and liquid medium. Optical absorption and bandgap of these nanocolloids were tunable. Abstract: Pulsed laser ablation in liquid medium (PLALM) is a nanofabrication technique to produce complex nanostructures. CuInGaSe2 (CIGS) is an alloy with applications in photovoltaic industry. In this work, we studied the effects of laser ablation wavelength, energy fluence and liquid medium on the properties of the CIGS nanoparticles synthesized by PLALM. The nanoparticles obtained were analyzed by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS) and UV–vis absorption spectroscopy. XPS results confirmed the chemical states and composition of the ablated products. TEM analysis showed different morphologies for the nanomaterials obtained in different liquid media and ablation wavelengths. The optical properties for these CIGS nanocolloids were analyzed using UV–vis absorption spectroscopy. The results demonstrated the use of PLALM as a useful synthesis technique for nanoparticles of quaternary photovoltaic materials.